Iranian consensus on use of vitamin D in patients with multiple sclerosis. Issue 1 (December 2016) - Jahromi, Soodeh; Sahraian, Mohammad; Togha, Mansoureh; Sedighi, Behnaz; Shayegannejad, Vahid; Nickseresht, Alireza; Nafissi, Shahriar; Mohebbi, Niayesh; Majdinasab, Nastran; Foroughipour, Mohsen; Etemadifar, Masoud; Moghadam, Nahid; et al.
Abstract Background Accumulating evidences from experimental, epidemiologic and clinical studies support the potential linkage between poor vitamin D status and the risk of developing Multiple Sclerosis (MS), as well as, an adverse disease course. However, the results of the trials on the clinical outcomes of vitamin D supplementation in MS patients are less consistent which brought many discrepancies in routine practice. In this article we presented a summary of a symposium on vitamin D and MS. In this symposium we aim to review the current data about the relationship between vitamin D and MS, and suggest management guides for practicing neurologists. Discussion Generally, supplementation seems to be reasonable for all MS and clinically isolated syndrome (Rinaldi et al., Toxins 7:129–37, 2015) patients with serum 25(OH)D level below 40 ng/ml. In patients with vitamin D insufficiency or deficiency, a large replacing dose (e.g. 50, 000 IU capsules of D per week for 8–12 week) is recommended. Panel also suggested: the checking of the serum vitamin D, and calcium level, as well as, patients' compliance after the initial phase; a maintenance treatment of 1500–2000 IU daily or equivalent intermittent (weekly, biweekly or monthly) Dose, considering the patient's compliance; routine check of serum vitamin D level at least two times a year especially at the beginning of spring and autumn; Serum vitamin D evaluation for first degree relatives of MS patients at high risk age and supplementation in case of insufficiency (25(OH)D less than 40 ng/ml); correction of vitamin D deficiency and insufficiency before pregnancy, as well as, a daily dose of 1500–2000 IU or equivalent biweekly intake in 2nd and 3rd trimesters; stopping supplementation if 25(OH)D serum level exceeds 100 ng/ml. Summary Although the results of high power studies are not available, correcting vitamin D status seems plausible in all MS and CIS patients. Maintaining the serum 25(OH)D level between 40 and 100 ng/ml is not known to exert adverse effect. More ever, it might be associated with lower disease activity.